Florilegia Syriaca: Mapping a Knowledge-Organizing Practice in the Syriac World - Fiori, Emiliano; Ebeid, Bishara (Brill, 2023)
From the 6th century onwards, Syriac patristic florilegia - collections of Greek patristic excerpts in Syriac translation - progressively became a prominent form through which Syriac and Arab Christians shaped their knowledge of theology. In these collections, early Greek Christian literature underwent a substantial process of selection and re-organization. The papers collected in this volume study Syriac florilegia in their own right, as cultural products possessing their own specific textuality, and outline a phenomenology of Syriac patristic florilegia by mapping their diffusion and relevance in time and space, from the 6th to the 17th century, from the Roman Empire to China.